The contributions of the MUNA network to CUCS Naples 2022. Proceedings of the MUNA sessions - Sammartino, Gilberto (Culture of diversity, 2022)
The Muna Consortium (Mediterranean and Middle East University Network Agreement) was founded in 2015 and renewed in 2021, when 30 Universities coming from all Countries of Mediterranean area and some others from Middle East signed the Framework Agreement. As written in the Framework Agreement, also in this Muna space in the CUCS Conference, we propose three different main themes: MARE NOSTRUM (our Sea, the Mediterranean), PERSONA (Man) and ORBIS (the Earth), to summarize the proposals of Cooperation between Muna Network Universities. The first session is dedicated to the field of ORBIS to share the sustainability, through the biodiversity as a key element for the development of soil in different aspects as agricolture, fauna and flora sustainable management, with impact in the field of veterinary. Neverthless, a focus is also related to the inclusion and integration in the sustainable cities during this time of pandemia and migration flows with regard to the problem of clima changes in the Mediterranean area. The second session is focused on PERSONA, to share the experiences in the primary immunodeficiency inborn with the contributions of different Universities of different mediterranean area, examinating approaches of prevention and treatment, also thorough the proposal of a comparative study. Culture differencies in this pandemia period and the situation of human rights in the mediterranean basin are discussed. The last item is MARE NOSTRUM, foused on exploitation of the Mediterannean resources proposed by International Cooperations among Muna Partners. Besides the exploitation, the themes of improving the quality of water, the safeguarding of ittic sector and the mandatory better organization of port areas are further developed. In conclusion, a round table discusses the opportunities of the Cooperation, especially to understand which proposals can be followed in the Universities Cooperation and maybe to establish future projects.